2019
DOI: 10.1177/1350508419838692
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking work-family balance barriers and strategies among working fathers in the workplace

Abstract: This article explores the barriers and strategies experienced by Spanish working fathers regarding work-family balance. Based on 29 in-depth interviews with Spanish working fathers in different types of organizations and sectors, the results of this study present different barriers that are divided into three groups: contextual barriers, organizational barriers and internalized barriers. The results also suggest that the study’s participants fall into three categories or patterns: hegemonic gender order confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 49 publications
1
33
0
1
Order By: Relevance
“…However, organizational barriers affect men to a greater extent than women (Duvander, 2014). Recent studies have suggested that men who use flexible policies for caring reasons suffer from such flexibility in a manner associated with greater risks of career penalties (Belope-Nguema et al, 2018; Coltrane et al, 2013; Rudman & Mescher, 2013; Tanquerel & Grau-Grau, 2019).…”
Section: Labor-market Conditions and Gender-role Attitudes: Two Compementioning
confidence: 99%
“…However, organizational barriers affect men to a greater extent than women (Duvander, 2014). Recent studies have suggested that men who use flexible policies for caring reasons suffer from such flexibility in a manner associated with greater risks of career penalties (Belope-Nguema et al, 2018; Coltrane et al, 2013; Rudman & Mescher, 2013; Tanquerel & Grau-Grau, 2019).…”
Section: Labor-market Conditions and Gender-role Attitudes: Two Compementioning
confidence: 99%
“…Fathers often report feeling worried and even embarrassed to use offered leave entitlements (Koslowski and Kadar-Satat 2019;Moran and Koslowski 2019). Fathers are worried about what it might mean for their career prospects if they go against what is normal in their workplace (Rudman and Mescher 2013;Tanquerel and Grau-Grau 2020). A number of policies can help with this, including making sure fathers have adequate cover for their job responsibilities whilst on leave, and insuring that individual line managers support a father's efforts to combine work and family life (including being aware of who is a father of an infant).…”
Section: Supporting Fathers In the Workplace To Take Leavementioning
confidence: 99%
“…In the United States, where there is no statutory right to paid leave, studies suggest that men who are open about balancing their work and family devotions are vulnerable to "not man enough" harassment and other forms of social backlash for their failure to conform to traditional gender norms (Berdahl and Moon 2013;Rudman and Mescher 2013;Thébaud and Pedulla 2016;Vandello et al 2013). As discussed by Koslowski and O'Brien, fathers in countries with statutory rights to remunerated leave commonly report a sense of unease about being perceived as putting caregiving ahead of paid work even for short amounts of time and especially when they are in senior management roles (Brandth and Kvande 2002;Koslowski and Kadar-Satat 2019;Moran and Koslowski 2019;Närvi and Salmi 2019;Tanquerel and Grau-Grau 2020).…”
Section: Work Practicesmentioning
confidence: 99%
“…A growing body of evidence suggests that the propensity of working dads to invest time and energy in engaged fatherhood is significantly influenced by the perceived supportiveness of their work environment, particularly their supervising managers (Humberd et al 2015;Moran and Koslowski 2019;Stropnik et al 2019;Tanquerel and Grau-Grau 2020). Within this volume, Bosch and Las Heras report evidence that Latin American fathers' propensity to participate in family life (e.g., eat dinner at home) depends on the extent to which they benefit from Family Supportive Supervisor Behaviors (FSSBs) (e.g., managers who role model work-family balance).…”
Section: Work Practicesmentioning
confidence: 99%